Long-term variability study of total column ozone over Nigeria using multi-sensor reanalysis measurements - A. B. Rabiu; S. T. Ogunjo; A. Akerele; O. E. Dare-Idowu (Discover Geoscience)
Abstract This study investigated the long-term changes in the total column ozone (TCO) over Nigeria using measurements retrieved from the ozone (O3) multi-sensor reanalysis (MSR). It assessed the spatial variability of TCO in Dobson Unit (DU), its monthly distribution, and interannual variability, and identified trends at these time scales over three decades (1981–2010) using the Sen’s slope estimator. The results of these analyses reveal that over the study area, the O3 maximum and minimum concentrations are 248 DU and 268 DU, respectively, producing an average range of about 255 DU. During the dry season, TCO values were found to be less than 250 DU across the country but greater than 250 DU during the wet season. Furthermore, the interannual O3 characteristics uncover dynamic oscillating features, which can be attributed to the influence of a combination of many atmospheric processes, e.g., the wind pattern and stratospheric intrusion. The contribution of sunspot number, Southern Oscillation Index, and Quasi Biennial Oscillation (QBO) at 10 hPa and 30 hPa to TCO values across Nigeria was also investigated. QBO at 10 and 30 hPa showed statistically significant correlation values with TCO over the region.